Struktur Naskah Ludruk Lakon Mliwis Hitam - Tafsir Hudha (Institut Seni Indonesia Surakarta, 2020)
This research is entitled Analisis Struktur Naskah Ludruk Lakon Mliwis Hitam. This research focused on documenting folk theater in form ofwriting manuscript and the structural analysis. The script will no longer be developed into a wos, but into a modern structure one. The existence of Mliwis Hitam script is become an affirmation of folk art embodying solicitation of theater spirit in Nusantara. It is worthwhile that it can emerge new idiom to enrich kinds of theater in Indonesia. Structural analysis of Mliwis Hitam script is also done to ease director and actors to understand the story. This analysis can also be a reference in transformation process from textual script into a dramatic scene on stage.